The equine tendon in health and disease (Animal science, issues, and professions series., 2013)
This book is designed to provide information on all aspects of clinical management of tendon problems in horses. The chapters cover the spectrum of understanding structure and function, diagnostic modalities, treatment options, rehabilitation strategies, etiology of injury, and prevention of tendon injury. All authors have vast clinical experience and are among the most qualified in their respective areas of expertise. It is the editor's goal to provide the reader with a state of the art resource that will aid in dealing with tendon problems. This includes diagnosing and treating the acute inj.